Correlation of lipid profile with diastolic dysfunction in normotensive young patients under 40 years of age - Jain, Naman; Kuwer Devi Singh,; Gupta , Himanshu; Umesh Pratap Singh,; Sharma, Sanjeev (Asian Journal of Medical Sciences, 2023)
Background: Diastolic dysfunction in young adults is associated with increased morbidity and mortality. The identification of risk markers associated with diastolic dysfunction could allow for targeted primary prevention efforts. Aims and Objectives: The aim of the study was to study whether dyslipidemia is associated with diastolic dysfunction independent of systemic hypertension in young patients under 40 years of age. Materials and Methods: This was a cross-sectional analytical study done from April 2021 to March 2022 in SSMC and SGMH Rewa (M.P.), 214 normotensive cases under 40 years of age were taken as cases by simple random sampling. Sample size calculated by standard formula with confidence level of 95% and margin of error was <5%. Lipid profiles (S. Triglyceride [TG], S. Cholesterol, and S. low-density lipoprotein [LDL]) of all the patients were checked. 2D echocardiogram of patients was done to check for diastolic dysfunction. All data were compiled and compared with the previous studies. Results: We found that the prevalence of diastolic abnormalities in adults under 40 years of age was 21.9%. It was found that there was significant correlation between dyslipidemia and presence of diastolic dysfunction in patients. Patients with higher than normal levels of S. TG, S. Cholesterols, and S. LDL were found to have more prevalence of diastolic dysfunction then patients with normal levels of S. TG, S. Cholesterols, and S. LDL. Higher grades of diastolic dysfunction were found in patients with dyslipidemia as compared to patients without dyslipidemia. High levels of TG and LDL and even Borderline high levels of LDL can be good predictors of diastolic dysfunction. Conclusion: Dyslipidemia is associated with diastolic dysfunction in young patients even without systemic hypertension.